ANALYSIS OF DEBT TO TOTAL ASSET RATIO AND RETURN ON ASSET TO FINANCIAL PERFORMANCE OF PT INDOFOOD SUKSES MAKMUR TBK - Putri Indah Sari; Nurhayati Nurhayati (Jurnal Ekonomi, 2023)
This study aims to analyze Debt to Total Asset Ratio and Return on Asset in Assessing Financial Performance at PT. Indofood Sukses Makmur Tbk. This research was taken from PT. Indofood Sukses MAkmur Tbk. The type of data used in this study is quantitative data in the form of financial statement documents of PT. Indofood Sukses Makmur Tbk. Year 2018 to 2022 taken from the Indonesia Stock Exchange website. The data sources used in this study are external data sources, namely data obtained indirectly. The analysis used in this study is qualitative descriptive analysis. The approach used to achieve the research objectives is to analyze the Debt to Total Asset Ratio and Return on Assets. So that the company can optimize its assets to obtain the desired profit. The results of this study show that (1) the company's DAR is good, this can be seen from the standard DAR criteria which are less than 90%. (2) The company's ROA is good enough, because the company has been able to manage its assets effectively.